Avaliação dos efeitos causados pelas diferentes condições de cultivo nas microalgas Scnedesmus sp. e Chlorella sp. mediante a potencialização de teor lipídico - Chiesa, Jaqueline Elise Garcia (2019)
Biofuels are commonly used as a fuel derived from biological materials, including non fossilized dead organic matter, and also likely from metabolic products from living organisms, such as vegetable oil for biodiesel production. Among the raw materials used for biodiesel production, it is found as microalgae that has been pointed as a promising alternative of raw material, in relation to others. In this context, the present study aims to optimize the cultivation conditions of the microalgae Chlorella sp and Scenedesmus sp, besides verifying the growth of these species when cultivated at different levels of nitrate, iron, zinc and biotin. The cultivation and maintenance of the inoculum, which occurred in the restoration of horizontal acrylic planes, kept at room temperature of 25 a 30° C, with photoperiod driver at 12 hours of light and 12 hours of dark, using three white fluorescent lamps of 40w was used in chu synthetic medium. Different nutrients, biotin addition and distinct microalgae species were selected as optimized for algal growth and lipid yield. Thus, to reduce the time and number of experiments, use factorial design 23e or central composite design. After the preliminary tests and the first stage of the adopted experimental model, the results indicate that the experimental methodology for the cultivation of microalgae Chlorella sp., Shows better results in the lipid content when carried out in the bath with nitrogen reduction. and iron with biotin addition. reaching a maximum value of 51.54% of lipid content, verified even with a number of days (time) showing the tendency of lipid volume increase in 20 days of cultivation. It is necessary to follow up the experiments in search of further improving the cultivation conditions employed, to enable better results in the tests in general.